Simulasi Algoritma Rerouting dan Prosedur Contention Controller pada Sistem Penyambungan ATM - Yudhitya Sorrenti; Wahyul Amien Syafei; Imam Santoso (Departemen Teknik Elektro, Universitas Diponegoro, 2012)
An ATM (Asyncronous Transfer Mode) switching system is designed to operate at high speeds and can serve a variety of traffic type with quality services. One of the technology could improve the performance of an ATM connection is rerouting algorithm include Controller Contention procedure as the procedure of operation. Rerouting algorithm is an algorithm that is able to overcome the routing conflict at a certain level, and restore the routing according to destination address. Contention Procedure Controller is a controller that is located in the connection element is used to determine the route, can proceed or not. This procedure is found on the rerouting algorithm using Banyan networks that have a single point in the framework of connections in ATM switching. In this research a simulation was designed to simulate the rerouting algorithm both without conflict and with conflict at various levels. Controller Contention Procedure aims to provide a detailed description when conflicts occur in switching elements and the duty to select ATM routing cells based on its RNS value. This procedure should refer to the rerouting algorithm and generate output according to the algorithm. Keywords: rerouting algorithm, Contention Controller, ATM switching, Banyan network.